Fertilizer policy in Thailand - Chitibut, Wannarut; Poapongsakorn, Nipon; Aroonkong, Danop (International Food Policy Research Institute, 2014)
Fertilizer use in Thailand has become an integral part of agriculture due to the declining availability of arable land and the increasing role of rice and other agricultural exports in the economy. Approximately 47 percent fertilizer is used on rice, production of which has increased from 13.4 million MT to 36 million MT from 1970 to 2010 coinciding with a rise in fertilizer consumption from .2 million MT to 2.6 million MT. However, Thailand has a limited supply of raw materials for fertilizer and therefore imports both raw materials and pre-compounded grades for domestic production and distribution. This brief reviews the Thai fertilizer sector and the changes in policy which have led to its growth.